Efektivitas Model Inquiry-Based Learning Berbantuan Virtual Laboratory dalam Pembelajaran Fisika: Tinjauan Literatur - Lutfiatussolihah Lutfiatussolihah; Aulia Aulia; Robiatul Adawiah; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Teacher Education, 2023)
This study aims to analyze the effectiveness of Inquiry-Based Learning supported by a virtual laboratory in physics education. The study employed a literature review method using a qualitative descriptive approach, involving the identification, selection, and synthesis of 15 articles published between 2014 and 2023. The results of the analysis indicate that the implementation of Inquiry-Based Learning supported by virtual laboratories consistently enhances students’ conceptual understanding, scientific process skills, and critical thinking abilities. This effectiveness is influenced by the type of inquiry model used, the characteristics of the virtual media, and the learning strategies applied. The integration of inquiry-based learning with digital technology creates a more interactive, exploratory, and meaningful learning experience. Thus, this approach can serve as an effective alternative in physics education, particularly to address laboratory facility limitations and improve the quality of students’ learning processes and outcomes.